Academic Supervision Model for the Early Childhood Education in the Municipality of Semarang - Latiana, Lita; Samsudi, Samsudi; Pranoto, Sugiyo; Slameto, Slameto (Universitas Negeri Semarang, 2017)
This study aims to describe the model of academic supervision for the Early Childhood Education (PAUD) that has been implemented so far. The research subjects consist of supervisors, principals, and teachers of the early childhood education in the municipality of Semarang. Data were drawn using interviews, questionnaires, and documentary studies. The data were then analyzed employing descriptive analysis. This research used non-probability sampling technique with purposive sampling.The results show that the supervisory activities carried out during this time were still separated from the elements of supervision, there has been no collaboration between supervisors, principals, and teachers in the planning, implementation, method, and follow-up activities. During this period of time, the supervisors performed their duties based on work programs that had been designed without any input which was needed by the teacher, and there was no opportunity to inform obstacles during the learning process and there was no communication with the supervisor. This has made the supervision activities were not on the basis of the teachers’ problems but rather on the basis of the academic supervision activity for the PUD there is no good cooperation and communication between the supervisor, principal, and teacher; the supervision is still separated and there is no collaboration. It is recommended to realize the need for the development of collaborative-based supervision model in PAUD institutions so that the supervision activities are in accordance with the needs of teachers in learning.